SLANG WORDS IN INSTAGRAM - Oktaviani Simbolon; Army Maranata Sinaga; Andi J. Silitonga (LPPM Universitas Darma Agung, 2021)
The objectives of the study are to find out the words of slang words on Instagram, to find out the most dominant word of slang words on Instagram, and also to find out the reason for the dominant word in Instagram. This study applies qualitative and quantitative research methods. This study finds that there are 78 slang words found in Instagram; U, Ur, Yall/ y’all/ yal, Missin, Dressin, BAKKKK, Chill, Tho, Livin Lifeee, homie, Gotta, N, Goooooo, LIT/litty, Bts, Da, Bc, Bro/Bro’s, Unc, Pops, LOL, Kinda, Gonna, Tf, Til/till, Ppl, Fave, Pls, Af, Duckin, Gon’, Givin, Pic, Lil, Yooooo, Fuckin, Cuammm on, Gonna, #tbt, Sickkkk, ZOOONNEE, Deeeepppp, Convos, Gooood, Talkin, Brunch, Thang, Bossman, BTW, Cuz, Em, Ain’t/#aintpeace, Bday, Babe, Ya, Congrats, Tatt, Imma, Makin, #fuck, #swagwars, Wanna, Whoopin, C’mon, Workin, Dis, Mudda Sukka, SISTA, BLM, Bi**h, FOPA, OWAAAT, Joiiiwwnnntttttttzzzz, muthaf*kkin’, ICYMI, Asf, Poppin, and Sleepin. The most dominant word on Instagram was Yall/y’all/ yal (you all). The reasons for the dominant word of slang words on Instagram are to entertain others, keep up with the times, even to reduce or to dispel solemnity or pomposity of conversation.